Karakteristik Dupa Aromaterapi dari Campuran Cangkang Kelapa Sawit dengan Bubuk Serai dan Variasi Perekat - Aidah Adzra Pratama; Sunardi; Ida Bagus Banyuro Partha (Program Studi Teknologi Hasil Pertanian, 2026)
Aromatherapy incense is a type of incense made from natural ingredients that when burned produces a certain aroma with the aim of providing a relaxing or therapeutic effect. The purpose of this study was to determine the effect of mixing shells and lemongrass powder and the type of adhesive on the quality of aromatherapy incense and to find out which incense produces a longer burning rate and is most preferred. In this study, a research method was used with an experimental design, namely a Randmized Complete Bloc Design (RCBD) of two factors, the first factor was the ratio of palm shell powder to lemongrass powder consisting of 3 levels (2: 1, 1: 1, 1: 2) and the second factor was the variation of adhesive consisting of 3 levels (gondorukem, damar resin, pine resin) with two repetitions. The results of this study indicate that the ratio of palm shells to lemongrass powder significantly affects the burning rate of incense, the type of adhesive affects the water content, and does not affect the ash content and density. The comparison of palm shells with lemongrass powder (1:2) in sample A3 and pine resin adhesive (B3) produced incense with the highest level of liking, and the lowest burning rate of 0.0414 g/minute.